Supercontinent Dynamics and Biogeochemical Cycles: The Vital Interplay of ‘Life and Death’ - Sharma, Ayush; Ahmed, MM (Journal of Advanced Research in Geo Sciences & Remote Sensing, 2024)
Supercontinents have significantly impacted mantle dynamics, solid Earth processes, surface environments, the biogeochemical cycle. In the early history of Earth, the collision of parallel intra-oceanic arcs was crucial for building embryonic continents. Super downwelling along Y-shaped triple junctions may have contributed to the rapid assembly of continental fragments into closely packed supercontinents. The reassembly of supercontinents after breakup and ocean closure occurs through “introversion”, “extroversion” or a combination of both. The assembly of supercontinents also had a significant impact on life evolution, with the Cambrian Gondwana assembly playing a role in promoting biodiversity. Recent models suggest a relationship between superplumes, supercontinent breakup, mass extinction. The assembly and dispersal of continents appear to have influenced the biogeochemical cycle, but whether these stages are closely linked to solid Earth processes remains to be investigated